First results from the TNG50 simulation: galactic outflows driven by supernovae and black hole feedback - Nelson, Dylan; Pillepich, Annalisa; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present the new TNG50 cosmological, magnetohydrodynamical simulation - the third and final volume of the IllustrisTNG project. This simulation occ
Gesehen am 12.02.2020